2008
DOI: 10.4049/jimmunol.181.1.299
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Help Regulates Expression of Crucial Genes Involved in CD8 T Cell Memory and Sensitivity to Regulatory Elements

Abstract: The role of CD4 help during CD8 memory differentiation has been clearly demonstrated in different experimental models. However, the mechanisms involved to mediate CD4 help and the extent of its effects remain largely unknown. Using gene analysis at a single cell level, which allows the study of gene expression in terms of frequency, intensity and coxpression, we show that unhelped CD8 T cells harbor severe defects in the expression of crucial genes involved in proliferation, survival, and cytotoxic functions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…Using the tetramer assay, all the mice were monitored for CTL survival and memory CTL expansion after boosting with DCova (Figure 1b). In both WT and CD4 + T cell-deficient mice, CTLs which received help during priming demonstrated significantly stronger survival and expansion upon boosting ( P <0.05), corroborating previous observations [6,7,9,10]. Interestingly, transitionally helped effector CTLs also survived and expanded more efficiently than unhelped CTLs both in WT and CD4 + T cell-deficient mice ( P <0.05).…”
Section: Resultssupporting
confidence: 88%
“…Using the tetramer assay, all the mice were monitored for CTL survival and memory CTL expansion after boosting with DCova (Figure 1b). In both WT and CD4 + T cell-deficient mice, CTLs which received help during priming demonstrated significantly stronger survival and expansion upon boosting ( P <0.05), corroborating previous observations [6,7,9,10]. Interestingly, transitionally helped effector CTLs also survived and expanded more efficiently than unhelped CTLs both in WT and CD4 + T cell-deficient mice ( P <0.05).…”
Section: Resultssupporting
confidence: 88%
“…Indeed, these studies have shown that CD8 + T cells primed under helpless conditions have severe defects in the expression of crucial genes related to proliferation, survival and cytotoxic functions (Rapetti et al, 2008). We have now extended these observations to demonstrate that T-cell responses generated in helpless mice following vaccination are qualitatively inferior when compared with helped mice and fail to afford resistance against viral challenge.…”
Section: Epstein-barr Virus (Ebv) Vaccinesupporting
confidence: 50%
“…Increasing evidence from animal studies and clinical trials have suggested that effective adoptive cellular immunotherapy (ACI) is not limited to the use of CD8 + T cells and may be enhanced by the use of antigen-specific CD4 + T cells (2425). For examples, immunotherapy using tumor-specific CD8 + T cells in CD4-deficient MHC II −/− mice resulted in regression of pulmonary metastases, but did not result in long-term antitumor immunity and tumor eventually recurred (26, 27).…”
Section: Discussionmentioning
confidence: 99%